Resolution Funding : Who Pays When Financial Institutions Fail? - Croitoru, Oana (Technical Notes and Manuals; Technical Notes and Manuals ;, 2018)
A key element of the international reform agenda since the Global Financial Crisis has been to strengthen resolution regimes and make government bailouts the last, not first, resort. A new international standard prescribes a range of tools, powers, and funding arrangements needed to resolve 'any financial institution that could be systemically significant or critical if it fails.' It recommends having resolution funding arrangements set up in advance, 'so that authorities are not constrained to rely on public ownership or bail-out funds as a means of resolving firms.' It leaves open significant flexibility with respect to the arrangements that would provide the resources authorities will need to carry out effective resolution. This paper offers a framework for weighing the relative advantages of different resolution funding options that could meet the standard. It presents the main developments to date and discusses the advantages and disadvantages of different options.